PERLINDUNGAN TERHADAP PEMEGANG SERTIPIKAT HAK MILIK YANG DIBATALKAN DENGAN BUKTI GIRIK DALAM PUTUSAN PENGADILAN TATA USAHA NEGARA NOMOR 61/G/2021/PTUN.SRG. - Raini Nurhaedah; Benny Djaja (Fakultas Hukum Universitas Tarumanagara, 2022)
A land dispute is a problem in the land of everyone who feels the owner of the land object isdisputed by the two litigants. Land disputes themselves often occur in people's lives from the pastuntil now. Because land is a complex and vital object when discussed, land itself is one of theobjects that is indispensable for the survival of living things that are used for farming or a placefor shelter. In this study will be discussed about land disputes. The definition of soil itself is a partof the earth's crust that has an arrangement of minerals and organic matter contained in it. One ofthe issues to be discussed is the protection for canceled certificate holders with girik evidence inthe Serang State Administrative Court Decision Number 61/G/2021/Ptun.Srg. in the content of hisdecision stated that the judge decided to require the defendant to cancel the certificate ofownership of the intervention defendant and granted the plaintif 's claim in this case the owner ofthe girik evidence base, and the author wants to link the Judge's Decision with Article 32paragraph (2) Government Regulation Number 24 of 1997 concerning Land Registration and alsowith other articles related to the case. The purpose of this study is to provide readers with anunderstanding of the forms of protection in land disputes. The research method used in answeringthe problems in the research uses normative juridical legal research methods.